Critique to The Logic and The Normative Senses of Positive Accounting Theory - Suwaldiman Suwaldiman (Sinergi: Kajian Bisnis dan Manajemen, 2003)
This essay argues that Positive Accounting Theory (PAT) is not better than other forms of theorizing though the supporters of PAT claim that PAT avoids normative statements. PAT as claimed by Watts and Zimmerman is free of value, just explains and predicts accounting practice. They also claim that PAT answers what is and why, not what should be nor how to do. In contrast normative accounting theory tries to answer what should be done by accounting practices to contribute the social change (i.e. social welfare distribution). As a matter of fact what is claimed by PAT supporters is not true because accounting, as an applied discipline is impossible to be free of value. Accounting discipline must have such purpose orientation. Accounting theory will be meaningless if it just explains and predicts accounting practice without providing prescriptions. Therefore it is clear that PAT is not better than other forms because it still leaves too many questions unanswered and makes accounting to be meaningless.